2010
DOI: 10.1007/s00775-010-0644-z
|View full text |Cite
|
Sign up to set email alerts
|

The metal-binding properties of the blue crab copper specific CuMT-2: a crustacean metallothionein with two cysteine triplets

Abstract: Most crustacean metallothioneins (MTs) contain 18 Cys residues and bind six divalent metal ions. The copper-specific CuMT-2 (MTC) of the blue crab Callinectes sapidus with 21 Cys residues, of which six are organized in two uncommon Cys-Cys-Cys sequences, represents an exception. However, its metal-binding properties are unknown. By spectroscopic and spectrometric techniques we show that all 21 Cys residues of recombinant MTC participate in the binding of Cu(I), Zn(II), and Cd(II) ions, indicating that both Cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The resulting isosbestic points appearing at 232 and 260 nm indicate a step-wise formation of two different metallated products during the course of the cadmium titration at pH 7. It is noted that a similar bathochromic shift of 6 nm for the S − →Cd 2+ LMCT band was previously observed in the cadmium reconstitution of mammalian metallothionein-1 [66] and crustacean metallothionein-2 [67]. Such shifts were assigned to the deconvolution of the difference absorption spectrum of the AQ-C16C19 transition of a mononuclear tetrahedral complex of Cd 2+ with four terminal thiolates to a Cd-thiolate polynuclear site featuring bridging thiolate ligands [66].…”
Section: + Binding Properties Of Aq-c16c19 Studied At Ph ≥mentioning
confidence: 77%
“…The resulting isosbestic points appearing at 232 and 260 nm indicate a step-wise formation of two different metallated products during the course of the cadmium titration at pH 7. It is noted that a similar bathochromic shift of 6 nm for the S − →Cd 2+ LMCT band was previously observed in the cadmium reconstitution of mammalian metallothionein-1 [66] and crustacean metallothionein-2 [67]. Such shifts were assigned to the deconvolution of the difference absorption spectrum of the AQ-C16C19 transition of a mononuclear tetrahedral complex of Cd 2+ with four terminal thiolates to a Cd-thiolate polynuclear site featuring bridging thiolate ligands [66].…”
Section: + Binding Properties Of Aq-c16c19 Studied At Ph ≥mentioning
confidence: 77%
“…This MT-2 is 64 amino acids long, contains 21 cysteines and is characterized by two Cys-Cys-Cys triplets, each domain containing one triplet. In terms of MT-2’s metal-binding capacity, the fully Zn/Cd metallated thionein could present up to eight metal ions and up to 12 for Cu(I) [36]. Crustaceans present a particular Cu(I) oxygen carrier protein, haemocyanin, and should be characterized by specific homeostatic mechanisms.…”
Section: Unconventional Animalsmentioning
confidence: 99%
“…In Metazoans, MTs with one or more Cys-Cys-Cys triplets have been found in oligochaetes, mollusks and crustaceans [27][28][29][30][31]. Showing ability for preferentially binding Cu ions [32], these atypical forms of MT in mollusks and crustaceans have been associated with the presence of hemocyanin for oxygen transport, suggesting that these atypical MTs are involved in copper homeostasis associated with the synthesis and degradation of hemocyanin.…”
Section: Discussionmentioning
confidence: 96%
“…(in A, three biological replicates each consisting of three pooled tadpoles; in B, n = 3). three-metal or the four-metal thiolate cluster [31]. Circular dichroism and UV spectra performed on the b-domain of the human metallothionein 1b demonstrated that the additional cysteine positioned to form the cysteine triplet characterizing this isoform did not perturb the overall structure of the protein or the formation of the metalthiolate clusters [35].…”
Section: Discussionmentioning
confidence: 98%